1995
DOI: 10.1007/bf02253377
|View full text |Cite
|
Sign up to set email alerts
|

Potential stock differences in the social behavior of rats in a situation of restricted access to food

Abstract: The social behavior of outbred Long-Evans (LE) and Wistar (WI) rats was compared in a situation where access to food was particularly difficult (clearing an aquatic barrier, plus the necessity of carrying the food back to the home cage). In groups of either six WI or LE rats, only about 50% of individuals carried the food, and the others survived by attacking those that did. However, behavioral profiles associated with these acts were different in the two cases: LE carriers, contrary to WI carriers, restole so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The results of this study showed that a social differentiation appeared in all groups of rats exposed to the diving-for-food situation, each group being composed of an equal number of vehicle- and DZ-treated rats. The respective proportions of carriers and noncarriers were very close to 50%, which was consistent with previous studies (Colin & Desor, 1986; Helder et al, 1995; Krafft et al, 1994; Thullier et al, 1992). As previously shown (Schroeder, Collignon, et al, 1994; Schroeder, Humbert, Desor, & Nehlig, 1997; Schroeder, Humbert, Koziel, et al, 1995), early DZ treatment induced a loss of weight at the adult stage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study showed that a social differentiation appeared in all groups of rats exposed to the diving-for-food situation, each group being composed of an equal number of vehicle- and DZ-treated rats. The respective proportions of carriers and noncarriers were very close to 50%, which was consistent with previous studies (Colin & Desor, 1986; Helder et al, 1995; Krafft et al, 1994; Thullier et al, 1992). As previously shown (Schroeder, Collignon, et al, 1994; Schroeder, Humbert, Desor, & Nehlig, 1997; Schroeder, Humbert, Koziel, et al, 1995), early DZ treatment induced a loss of weight at the adult stage.…”
Section: Discussionsupporting
confidence: 92%
“…The apparatus used was described in previous articles (Colin & Desor, 1986; Helder et al, 1995; Krafft et al, 1994; Thullier et al, 1992). It consists of a home cage (40 × 40 × 40 cm) linked to an aquarium (150 × 25 × 40 cm) by a tunnel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation